Representasi Visual Kesehatan Mental Pada Serial Film Televisi Parasyte: The Grey (Analisis Semiotika Charles Sanders Peirce) - Fitra Nurary Arasyid Herliyan Putra (Tamilis Synex: Multidimensional Collaboration, 2024)
This study examines the visual representation of mental health in the television series "Parasyte: The Grey". Utilizing Charles Sanders Peirce's semiotic analysis approach, the research aims to uncover how aspects of mental health are visualized and interpreted within the context of the series' narrative. A qualitative research method is applied, with data collection techniques including documentation, observation, and literature study. Data analysis is conducted using Peirce's semiotic table consisting of sign, object, and interpretant, with a specific focus on character expressions and visual elements representing mental health conditions. The findings reveal that "Parasyte: The Grey" employs various visual signs to depict a spectrum of mental health conditions, ranging from anxiety and trauma to healing processes. These visual representations not only reflect contemporary understandings of mental health but also contribute to broader discourses on mental health representation in visual media. This research provides new insights into how television series can play a role in shaping public perceptions of mental health through complex and nuanced visual representations.